Leadership styles of middle managers in secondary schools / Haryati Basran - Basran, Haryati (2013)
Investigation into leadership styles is a widely debated and researched issue in the educational context. Nevertheless there is scant empirical research on leadership styles of middle managers in secondary school. Therefore, this study was conducted with the aim to identify the leadership styles of school middle managers in secondary school in the district of Sabak Bemam. The descriptive study comprised 125 teachers (here after refers as middle managers) from five secondary schools in Sabak Bemam district were randomly selected. The study employed a mixed method research design where data were collected via questionnaire survey and in- depth semi- structured interviews. The questionnaire used was the Multifactor Leadership Questionnaire (MLQ), adapted from Bass & Avolio (1992). A total of ten respondents were randomly selected from five secondary schools in the interview session. The quantitative data were analysed using Statistical Package for Social Sciences (SPSS) 17.00 version while the qualitative data were analysed deductively and inductively based on the research questions posed in this study. In order to see the types of leadership styles by middle managers in secondary schools, a frequency, percent, mean, standard deviation and T- test were used to test the data. The main findings of the study show that Transactional leadership style was the most preferred leadership style among school middle managers. Then it is followed by Transformational leadership style and Laissez- faire leadership style. Findings also indicated that there were no significant differences in leadership styles between male and female school middle managers in secondary schools. The analysis also revealed that there was no significant difference in leadership styles between novice and experienced school middle managers. Nevertheless, the findings revealed that there was a significant difference in the mean score for Laissez- faire leadership style between novice and experienced school middle managers. The findings imply that educational leaders especially middle managers need to be aware on their leadership styles as it is help to leader to build a good relation with the followers and retain a productive workforce. The overview of the evidence and findings of the study are used for some suggestions and recommendations for the future research.